Viability of creating an offshore wind energy cluster - Junqueira, Helena (2022)
Considering the advantages associated with the port sector concerning the potential of offshore wind energy, several international ports are aiming to achieve a solid integration in offshore wind energy clusters. This article performs an analysis of several seaports and offshore wind energy clusters in Europe to assess the feasibility of implementing an offshore wind energy cluster in the Port of Aveiro, Portugal. A deep literature review and a case study methodology were performed. Based on the analysis of the offshore energy market, and of the value chain of the company case study (ASM Offshore), it was concluded that the Portuguese market in this sector is not competitive, compared with other international markets. Nevertheless, the development of an offshore wind energy cluster could increase the included companie’s prospects, as well as dispute the growth of other companies associated with this sector. This research is relevant, because there is a lack of research that links the importance of seaports in offshore wind energy projects, in particular with a cluster structure, and because it contributes to knowledge for the development of the Aveiro region and Portugal, based on the exploitation of the renewable energy market and to the increase of related activities.